2022
DOI: 10.3389/fneur.2022.793080
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Tuberculous Meningitis and Pediatric Human Immunodeficiency Virus on the African Continent

Abstract: Biomarkers in body fluids are helpful objective tools in diagnosis, prognosis and monitoring of (therapeutic) responses of many neurological diseases. Cerebrospinal fluid (CSF) biomarkers are part of the diagnostic toolbox for infectious neurological diseases. Tuberculous meningitis (TBM) and Human immunodeficiency virus (HIV), are important burdens of disease in Africa and can negatively affect brain health. Two thirds of the world's population of people living with HIV reside in sub-Saharan Africa and 25% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…Previous work on biomarkers, including GFAP, analyzed only the CSF, not serum from viral encephalitis cases, and none used an FDA-approved assay (25)(26)(27)(28)(29)(30). Early identification of sepsis-associated encephalopathy, one of the most serious clinical manifestations of sepsis (31), would provide a more accurate diagnosis and prognosis, which now relies on nonspecific clinical manifestations and imaging features, often followed by lumbar punctures and electroencephalograms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on biomarkers, including GFAP, analyzed only the CSF, not serum from viral encephalitis cases, and none used an FDA-approved assay (25)(26)(27)(28)(29)(30). Early identification of sepsis-associated encephalopathy, one of the most serious clinical manifestations of sepsis (31), would provide a more accurate diagnosis and prognosis, which now relies on nonspecific clinical manifestations and imaging features, often followed by lumbar punctures and electroencephalograms.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 has also been implicated in promoting fibroblast development and subsequently, pulmonary fibrosis [23,24]. Elevated IL-6 expression was also reported in pleural fluid of TB patients as well as in cerebrospinal fluid (CSF) in patients with TB meningitis [25][26][27]. While IL-6 is predominantly associated with disease severity in TB, knockout studies have shown that IL-6 plays an important role in controlling bacterial load early in the infection through induction of protective interferon gamma-producing T cell responses [28].…”
Section: Discussionmentioning
confidence: 99%